Etude Prospective Du Profil Épidémiologique Des Femmes Enceintes Pré-Éclamptiques En Mauritanie - Mohamed, Mariem Sidi; Sass, Setty; Zein, Ahmed; Lbarae, Ahmed; Khadmaoui, Abderrazzak; Lrhorf, L. Aicha; Oumaima, Benharbit; Bengueddour, Rachid (European Scientific Journal, ESJ, 2017)
Pre-eclampsia is a major public health problem in pregnant women. The objective of our study is to describe the socio-demographic and epidemiological profile of pre-eclampsia women. As a result, we conducted a prospective study in the maternity ward of the CHEIKH ZAYED Hospital Center in Nouakchott, during the period from August 2015 to September 2016. In addition, 360 pregnant women were interviewed, 31% (n = 112) with complications of arterial hypertension. In addition, 50 patients among these hypertensive women were pre-eclampsia, of whom 46% were between 20 and 30 years of age, 52% were black and 82% had no fixed profession. Multiple pre-eclampsia gestures accounted for over half of the cases (62%). Nevertheless, contrary to the literature, our outcome results are much more alarming, which calls for an adequate and effective intervention to deal with this scourge.